Families’ Experiences with Newborn Screening: A Critical Source of Evidence - Grob, Rachel (The Hastings Center report, 2018)
Debates about expanding newborn screening with whole genome sequencing are fueled by data about public perception, public opinion, and the positions taken by public advocates and advocacy groups. One form of evidence that merits attention as we consider possible uses of whole-genome sequencing during the newborn period is parents’ (and children's) diverse experiences with existing expanded screening protocols. What do we know about this experience base? And what implications might these data have for decisions about how we use whole genome sequencing and how we assess its impact in the future? Although the broader literature on genetic susceptibility testing suggests that testing usually does not have adverse effects on children's psychosocial well-being, certain newborn screening results have been demonstrated to cause distress, alter behavior, and even to influence the formation of new parental and family identities.